Wigner distribution function and alienation coefficient‐based transmission line protection scheme. Issue 10 (25th March 2020) - Ola, Sheesh Ram; Saraswat, Amit; Goyal, Sunil Kumar; Jhajharia, S.K.; Rathore, Bhuvnesh; Mahela, Om Prakash
Abstract : This study presents an algorithm for detection, classification, and location of transmission line faults. A fault index based on features extracted from current signals using the alienation coefficient and Wigner distribution function has been proposed for the detection and classification of faults. Double line and double line to ground faults have been classified from each other using ground fault index based on negative sequence current. Statistical relations are proposed for the estimation of fault location using peak values of the proposed fault index. The results of different case studies established the effectiveness of the algorithm. The algorithm is found to be effective for providing protection to transmission line against various faults. This is achieved using current signals recorded on one terminal of the line. This makes the protection scheme less complex, fast and more economic due to the elimination of the requirement of communication channel and global positioning system synchronisation. The proposed protection scheme is also validated on a real‐time network of transmission utility. The effectiveness of the algorithm is established by comparing performance with reported algorithms.